Reviewing Language Curriculum and Materials Development for Senior High School Level - Nuni Yohaningsih (Journal of English Language Teaching and Cultural Studies, 2021)
This present study discusses the cycles of curriculum and materials development at SMAN 14 Kota Tangerang, Banten Province. The method used in this study was case study. Data collecting technique used observation, interview, and documentation. The research informants involved teachers and students at SMAN 14 Kota Tangerang. The data was analyzed through data display, data reduction, and conclusion drawing/verification. The result of the study shows that the implementation of curriculum and material development has been done based on the procedural steps mandated by the educational ministry, and it is done periodically as the routine activities in every academic year. The implementation involves needs and situation analysis; developing curriculum into syllabus, materials, and lesson plan; and standardizing the learning outcomes. The last, there are 13 recommendations served by the teachers and students regarding the development of language curriculum and materials at SMAN 14 Kota Tangerang.